Finding the Spirit in Learning: An Effective Approach in Islamic Education - Aqila Muthmainna; Abdullah Idi; Karoma, Karoma; Muhsien Sulaiman, Abdul (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2025)
Islamic education is intended not only as a means of knowledge transmission but also as a foundation for nurturing character and spiritual awareness. However, the learning process in many institutions has increasingly shifted toward cognitive and academic focus, often marginalizing its spiritual essence or ruh. This study aims to identify and analyze learning approaches that address this gap by revitalizing the spiritual core of Islamic education. Using a systematic literature review of peer-reviewed national and international publications from the past decade, this research highlights five key approaches: holistic-integrative, exemplary (uswah hasanah), contemplative-reflective, contextual value-based, and digital storytelling. These approaches were selected based on clear pedagogical indicators and consistent references across various studies. They align with the foundational objectives of Islamic education as formulated by scholars such as Al-Attas and Al-Ghazali. This study contributes to the discourse on Islamic pedagogy by recommending the structured integration of these approaches into curriculum design, instructional strategies, and professional teacher development programs.